Clinical applications and research progress of totally implantable venous access ports: a literature review - Huang, Xiao-Min; Li, Xia; Deng, Jie; Chen, Jiong; Qian, Liang (Frontiers in Oncology, 2025)
Totally implantable venous access port (TIVAP), a novel intravenous infusion system that is used for long-term intravenous treatment, has become increasingly popular among cancer patients undergoing chemotherapy and other patients requiring long-term intravenous infusions. This technology has been introduced into clinical practice in China, with successful results. Nevertheless, there are still certain problems; for instance, China has not set up a specialized regulatory agency to oversee research and set guidelines for the comprehensive life-cycle management of TIVAP. Additionally, there exists a disparity in standardized operations and complication management related to TIVAP, which has resulted in variable outcomes, complications, and patient satisfaction with TIVAP implantation across different medical units in China. Therefore, this article aims to provide a systematic overview of the clinical applications and maintenance of TIVAP, both domestically and internationally. Furthermore, this review investigated the latest strategies and associated research on TIVAP implantation and complication management, aiming to provide a basis for standardized surgical and maintenance procedures, protocols to minimize complications, and approaches for enhancing the overall quality of life for patients.